Current status of Bacille Calmette Guérin (BCG) immunisation in Europe – A ptbnet survey and review of current guidelines. Issue 38 (11th September 2015) - Dierig, Alexa; Tebruegge, Marc; Krivec, Uros; Heininger, Ulrich; Ritz, Nicole; Paediatric Tuberculosis Network European Trials group (ptbnet)
Abstract Background The incidence of tuberculosis (TB) and the use of Bacille Calmette-Guérin (BCG) vaccines differ significantly worldwide. Information regarding recent changes in BCG use and immunisation policies is difficult to access. Therefore, this study aimed to systematically collect up-to-date data on the use of BCG in Europe. Methods A web-based survey of members of the Paediatric Tuberculosis Network European Trials group (ptbnet) and Tuberculosis Network European Trials group (TBnet) was conducted between October 2012 and May 2013. Results A total of 89 individuals from 31 European countries participated. Participants from 27/31 (87%) countries reported to have a national BCG immunisation policy/guideline. Reported indications for BCG immunisation were: universally at birth (14/31; 45%), universally at older age (2/31; 6%), at birth for high-risk groups (12/31; 39%), at older age for high-risk groups (6/31; 19%), at older age for Mantoux-negative individuals (6/31;19%), for immigrants (4/31; 13%) and as a travel vaccine (10/31; 32%). Members from 11 (35%) countries reported changes in BCG policies in the previous 5 years: discontinuation of universal immunisation of infants/children (6/11), reintroduction of immunisation of high-risk children (3/11), and change in BCG vaccine strain (2/11). Members from 24/31 (77%) countries reported using BCG Denmark. Conclusions Immunisation policies regarding BCG vaccine exist in the majority of European countries. Indications for BCG immunisation varied considerably, likely reflecting national TB incidence rates, immigration and other factors influencing TB control strategies. Importantly, the considerable number of recent policy changes highlights the need for regular collection of up-to-date information to inform public health planning.